UJI AKTIVITAS ANTIDIABETRES MELLITUS (DM) TIPE 2 AANDROGRAFOLID DAN EKSTRAK TERPURIFIKASI HERBA SAMBILOTO (Andrographis paniculata (Burm.f.) nees.) MELALUI PENINGKATAN TRANSLOKASI PROTEIN GLUT-4 PADA OTOT PAHA TIKUS RESISTEN INSULIN - , Mohamad Andrie, Dr. Agung Endro Nugroho, M.Si., Apt ([Yogyakarta] : Universitas Gadjah Mada, 2012)
The type 2 diabetes mellitus-insulin resistance disease is a condition characterized by obesity (hyperlipidemia) to cause a signal interference GLUT-4 protein translocation to the membrane of muscle cells and desensitization of muscle and fat tissue to insulin. These conditions stimulate hyperglycemia and hyperinsulinemia. Scientifically Andrographis paniculata (Burm. f.) Nees can treat some diseases such as influenza, cancer, inflammation, HIV and even AIDS. Andrographis paniculata (Burm. f.) Nees containing flavonoids and lactone compound. In the lactone, the main components are andrographolide. This study aims to look at the effect of andrographolide and purified extract of Andrographis paniculata (Burm. f.) Nees as a type 2 antidiabetes mellitus-insulin resistance. The main parameters are measured as a determinant of type 2 antidiabetic activity of insulin resistance such as blood glucose levels, lipid levels (triglycerides, LDL, and cholesterol), and translocation of GLUT-4 protein in muscle cells of the thigh (soleus muscle) rats. The research was conducted using a completely randomized design direction. Test preparations were divided into groups of andrographolide (doses 1.5 and 4.5 mg/ kg BW), purified extract (dose 434.6 and 1303 mg/ kg BW), fat-fructose group (Na CMC 1%), metformin group (metformin 45 mg/ kg BW) and normal group. Test animals are type 2 diabetes mellitus-insulin resistance is made through the imposition of fructose and fat-rich food for 50 days. Insulin resistance test carried out by comparing the parameter values of insulin resistance normal animals and fat-fructose animals. From the results of statistical analysis using the Independent Sample t-Test on all parameters of insulin resistance, showed significant differences (p<0.05) at day-30 and-50 between normal rats and fat-fructose rats. This indicates that the fatfructose diet affects all insulin resistance parameters were significantly, which the rat fat-fructose indicated that type 2 diabetes mellitus-insulin resistance. When the test animals had been insulin resistance, the animals were treated andrographolide and purified extract of Andrographis paniculata (Burm. f.) Nees for 5 days. Statistical tests were conducted using a Paired Sample t-Test for decreased levels of glucose, triglycerides, LDL, and translocation of GLUT-4 protein appeared to have a value of p<0.05 means that there are significant differences between days 50 and 55. This indicates that andrographolide and purified extract can significantly increase the translocation of GLUT-4 protein in rat thigh muscle cells, lowering blood glucose levels, triglycerides, and blood LDL levels, except lower blood cholesterol levels cannot be achieved. Percent of power reduction in blood glucose levels, triglycerides, LDL, and translocation of GLUT-4 protein of each group were statistically tested using the Oneway Analysis of Varian (Oneway ANOVA) with 95% confidence level.